2012
DOI: 10.1051/0004-6361/201219128
|View full text |Cite
|
Sign up to set email alerts
|

The high-mass disk candidates NGC 7538IRS1 and NGC 7538S

Abstract: Context. The nature of embedded accretion disks around forming high-mass stars is one of the missing puzzle pieces for a general understanding of the formation of the most massive and luminous stars. Aims. We want to dissect the small-scale structure of the dust continuum and kinematic gas emission toward two of the most prominent high-mass disk candidates. Methods. Using the Plateau de Bure Interferometer at ∼1.36 mm wavelengths in its most extended configuration we probe the dust and gas emission at ∼0.3 , c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 82 publications
9
75
0
Order By: Relevance
“…While the naturally weighted NH 3 (1,1) shows a bit more extended emission, one sees a larger scale velocity gradient approximately in eastwest direction. In comparison to that, the higher resolution (robust weighting 0) image rather reveals a velocity gradient in northeast-southwest direction, which is consistent with previous the findings by Beuther et al (2012Beuther et al ( , 2013, Moscadelli & Goddi (2014), and Goddi et al (2015). Since we are mainly interested in the kinematics of the innermost central sources we concentrate in the following on the higher resolution data.…”
Section: Nh 3 and Ch 3 Ohsupporting
confidence: 87%
See 2 more Smart Citations
“…While the naturally weighted NH 3 (1,1) shows a bit more extended emission, one sees a larger scale velocity gradient approximately in eastwest direction. In comparison to that, the higher resolution (robust weighting 0) image rather reveals a velocity gradient in northeast-southwest direction, which is consistent with previous the findings by Beuther et al (2012Beuther et al ( , 2013, Moscadelli & Goddi (2014), and Goddi et al (2015). Since we are mainly interested in the kinematics of the innermost central sources we concentrate in the following on the higher resolution data.…”
Section: Nh 3 and Ch 3 Ohsupporting
confidence: 87%
“…Peter et al (2012) find companion separations between 400 and several thousand AU, stressing the necessity of high spatial resolution, Furthermore, Sana et al (2012) infer that multiple system interactions dominate the evolution of massive stars. Interferometer studies have revealed that most high-mass starforming regions fragment into multiple objects, suggesting that massive monolithic cores larger than several 1000 AU are rare, however, the degree of fragmentation varies (e.g., Cesaroni et al 2005;Beuther et al 2007bBeuther et al , 2012Zhang et al 2009;Bontemps et al 2010;Wang et al 2011;Rodón et al 2012;Palau et al 2013;Sánchez-Monge et al 2014;Johnston et al 2015). Even regions that remain single continuum sources down to arcsec resolution, mostly fragment on even smaller scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, therefore, time we resolve the structures where not only the massive dense cores but also the proposed embedded high-mass disks are expected to fragment (e.g., Krumholz et al 2007a). While the lower resolution 1.36 mm image in Beuther et al (2012a) consisted mainly of an unresolved point source with only very little extended emission at low intensities, the new 843 μm data now reveal substructure within the inner ∼3000 AU of the region. In addition to spatially resolving the central peak into an elongated structure with a subpeak about 0.3 (∼900 AU) north of the main peak ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The dashed contour shows the same negative levels. The thick full line presents the 4σ contour (1σ ∼ 29 mJy beam −1 ) from the 1.36 mm data presented in Beuther et al (2012a). Several potential disk and outflow axes reported in the literature are presented (Davis et al 1998;De Buizer & Minier 2005;Sandell et al 2009;Pestalozzi et al 2004Pestalozzi et al , 2009Sandell & Wright 2010, see Introduction for more details).…”
Section: Observationsmentioning
confidence: 99%